Kritik Satire dalam Kolom Komentar Instagram @kementeriankegelapan mengenai Program Makanan Bergizi Gratis: Kajian Pragmatik - Ni Made Risma Dwiantari; I Wayan Simpen; I Nyoman Suparwa (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to identify and determine the conversational implicatures that arise in the comment section of Instagram @kementeriankegelapan, which discusses the issue of poisoning related to the “Makanan Bergizi Gratis” (Free Nutritious Food) program. The research method used is qualitative with a pragmatic approach, which not only examines the surface meaning but also considers the context of the utterances. The theory applied in this study is the theory of implicature, specifically conversational implicatures. The data were obtained from the comment section of Instagram @kementeriankegelapan on posts concerning the poisoning issue of MBG (Free Nutritious Food). Data collection was conducted using the listening method (Simak) and the advanced technique of listening-without-participating in speech (simak libat bebas cakap). Data analysis used the referential identity method (padan referensial) with the advanced technique of selecting defining elements (pilah unsur penentu). The findings show that there are eight pieces of data in the form of conversations, each containing an idea or topic that specifically responds to the satirical post uploaded on the @kementeriankegelapan account regarding the MBG food-poisoning issue. The topics include: Azab (punishment), Tunggangan di Akhirat (conveyance/punishment in the afterlife), shouting “Long live Jokowi!”, MBG as a way to alleviate poverty, color codes, preventing fights/gang fights, maggots, and “licking”/being servile. Each of these topics has its own implicature.